Visual Design for Malay Consonants Pronunciation - Noh, Zakiah; Z. Z. Abidin, Siti; Aliman, Sharifah; Ardi, Norizah (International Journal of Engineering and Technology, 2018)
Numerous studies on text visualization have been long conducted around the world for distant and close reading. Nevertheless, in Malay language, a lot of research works on text visualization are focusing more on distant reading as compared to close reading. Thus, there is still lacking on determining textual feature for in-depth analysis of Malay texts. This paper discusses the Malay texts features that involve in designing the pronunciation of Malay consonants. The design process starts by analyzing articulation table and the standard articulation part of human mouth. The important parameters are identified from both sources in order to represent such data and symbols in a glyph visualization. Each glyph representation illustrates the simplified version of pronouncing the consonants. This research gives benefit to scholars who learn Malay language as a second language, specifically concentrating on pronouncing a precise Malay consonant.Â